Differences of hemodynamic responses in patients undergoing endotracheal intubation with conventional laryngoscope compared to video laryngoscope - Maryndianto, Dani (Jurnal SAGO Gizi dan Kesehatan, 2024)
Background: In general anesthesia, to facilitate the intubation process, laryngoscopy is used, with various shapes and sizes and additional functions such as use of video cameras, but it also comes with risks, one of which is a cardiovascular response.Objectives: To compare differences of hemodynamic responses (SBP= Systolic blood pressure, DBP= Siastolic blood pressure, HR= Heat rate, MAP= Mean atrial preassure, and RPP= Rate pressure product) in patients who undergoing endotracheal intubation with conventional laryngoscopes compared to video laryngoscopes at H. Adam Malik General Hospital.Methods: This is an analytical study with a pretest-posttest controlled group clinical trial design to compare differences of hemodynamic response in patients undergoing endotracheal intubation with conventional laryngoscope compared to video laryngoscope. All patients who underwent elective surgery under general anesthesia and endotracheal intubation and met the inclusion and exclusion criteria were included in the study.Results: This study showed a significant difference between the conventional laryngoscopy and video laryngoscopy groups on the results of systolic blood pressure measurements. While diastolic blood pressure at T0, T1, and T2 after laryngoscopy did not show significant differences. This significant difference was found at T1, where the HR of subjects in conventional laryngoscopy was significantly higher compared to video laryngoscopy.Conclusion: The use of a conventional laryngoscope for laryngoscopy and endotracheal intubation further enhances hemodynamic response compared to video laryngoscope, both when the glottis is visualized and when the cuff is inflated.